2021
DOI: 10.3389/fphar.2021.659215
|View full text |Cite
|
Sign up to set email alerts
|

Bletilla striata Polysaccharide Promotes Diabetic Wound Healing Through Inhibition of the NLRP3 Inflammasome

Abstract: The aim of this study was to evaluate the therapeutic effects of Bletilla striata polysaccharide (BSP) on wound healing in diabetes mellitus (DM) and to explore the underlying mechanisms. DM mouse models were induced by high fat-diet feeding combined with low-dose streptozocin injection. To establish diabetic foot ulcer (DFU) models, DM mice were wounded on the dorsal surface. Subsequently, mice were treated with vehicle or BSP for 12 days and wound healing was monitored. The effects of BSP on the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Oxidative Medicine and Cellular Longevity 9 Oxidative Medicine and Cellular Longevity Persistent NLRP3 activation in macrophages disrupts the transformation of the inflammatory M1 phenotype to M2 phenotype, which results in delayed healing of DW [57]. Treatment with Bletilla striata polysaccharide, the main active ingredient of Bletilla striata, promotes wound healing by suppressing the NLRP3 inflammasome, and as a result, induces a switch from the proinflammatory M1 phenotype towards the prohealing M2 phenotype [132]. The external use of glibenclamide can show similar pharmacological effects by inhibiting NLRP3 inflammasome activity and reducing the expression of inflammatory factors to downregulate the MI phenotype and upregulate the M2 phenotype [48].…”
Section: Therapeutic Targeting Of Nlrp3 Inflammasomementioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity 9 Oxidative Medicine and Cellular Longevity Persistent NLRP3 activation in macrophages disrupts the transformation of the inflammatory M1 phenotype to M2 phenotype, which results in delayed healing of DW [57]. Treatment with Bletilla striata polysaccharide, the main active ingredient of Bletilla striata, promotes wound healing by suppressing the NLRP3 inflammasome, and as a result, induces a switch from the proinflammatory M1 phenotype towards the prohealing M2 phenotype [132]. The external use of glibenclamide can show similar pharmacological effects by inhibiting NLRP3 inflammasome activity and reducing the expression of inflammatory factors to downregulate the MI phenotype and upregulate the M2 phenotype [48].…”
Section: Therapeutic Targeting Of Nlrp3 Inflammasomementioning
confidence: 99%
“…In RAW264.7 cells, BRP (5–200 μg/ml) stimulated the expression of iNOS, TNF-α, and IL-1β in concentration-dependent manner ( Diao et al, 2008 ). A recent study conducted in the diabetic mouse model found that 5% BRP solution (50 μl) treatment once daily could accelerate the diabetic wound healing via inhibiting the high glucose-activated NLRP3 inflammasome ( Zhao et al, 2021 ). Additionally, BRP could also be used for the treatment of oral ulcer ( Liao et al, 2019 ).…”
Section: Botanical Drugs In Traditional Chinese Medicine With Wound H...mentioning
confidence: 99%
“…The main components including Astragalus membranaceus [ 22 , 23 ], Salvia miltiorrhiza [ 24 ], and Safflower [ 25 ] and their extracts or monomers demonstrated the ability to upregulate the expression of VEGF/VEGFR2 in HUVECs and promote angiogenesis in vitro. The extracts or monomers of Angelica dahurica [ 26 ], Frankincense [ 27 ], Myrrh [ 28 ], and Bletilla striata [ 29 ] also showed antibacterial and anti-inflammatory effects in promoting wound healing. This is consistent with the theory of traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%